2020
DOI: 10.1021/acs.jcim.0c00236
|View full text |Cite
|
Sign up to set email alerts
|

Structural Determinants of the Dopamine Transporter Regulation Mediated by G Proteins

Abstract: Dopamine clearance in the brain is controlled by the dopamine transporter (DAT), a protein residing in the plasma membrane, which drives reuptake of extracellular dopamine into presynaptic neurons. Studies have revealed that the βγ subunits of heterotrimeric G proteins modulate DAT function through a physical association with the C-terminal region of the transporter. Regulation of neurotransmitter transporters by Gβγ subunits is unprecedented in the literature; therefore, it is interesting to investigate the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 60 publications
1
3
0
Order By: Relevance
“…A hydrogen bond was also formed between E586 (NET) and Y59 (Gβγ) at a distance of 1.92 Å, and W585 (NET) interacted with W99 (Gβγ) through van der Waals (VDW) interactions (Figure S1B). These findings are consistent with Rojas et al's (2020) and Pino et al's (2021) [14,22] study of the DAT/Gβγ interaction.…”
Section: Gβγ Binding To Net Induces Conformational Changes That Decre...supporting
confidence: 92%
See 2 more Smart Citations
“…A hydrogen bond was also formed between E586 (NET) and Y59 (Gβγ) at a distance of 1.92 Å, and W585 (NET) interacted with W99 (Gβγ) through van der Waals (VDW) interactions (Figure S1B). These findings are consistent with Rojas et al's (2020) and Pino et al's (2021) [14,22] study of the DAT/Gβγ interaction.…”
Section: Gβγ Binding To Net Induces Conformational Changes That Decre...supporting
confidence: 92%
“…Previous studies on the interaction between DAT and Gβγ have demonstrated that Gβγ activation leads to the efflux of DA through DAT. Computational studies have also described specific interactions between the carboxy terminus of DAT and Gβγ [14,22]. However, there is a lack of structural information regarding the potential effects of Gβγ on SERT or NET.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2a right panel), explaining their impaired reuptake. The mutations associated with psychiatric conditions affect DA efflux and involve interactions with other proteins such as Gβγ subunits of the G-protein for Glu602Gly in BP and Arg615Cys in ADHD or syntaxin for Arg51Trp in autism [ 66 , 67 ], affecting hDAT networking (see Supplementary Text for Fig. 2a ).…”
Section: Resultsmentioning
confidence: 99%